Quality improvement through 8D methodology: an automotive industry case study - Hetharia, Dorina; Rusman, Karyadi (Universitas Mercu Buana, 2025)
Nowadays quality is a key factor for the success of a product or company to survive and be accepted by consumers. Repeated quality problem in automotive industry become one of factor that influence company performance. However the problem is visual aspect, if this repetitive will increase customer dissatisfaction. Problem covers pillar loop scratch becomes the repeated and worst problem in Feb–March 2020. This research aims to assist in quality improvement by using the eight discipline (8D) method to solve the problem “cover pillar loop scratch. An 8D method is a problem-solving tool that has complete and systematic corrective action stages in problem-solving, which is for short-term action and long-term corrective action also effective in preventing the re-occurring problem. Result the implementation of the 8D methodology in problem-solving seat belt production problems in the SB3 line of Automotive Industry succeeded in reducing and eliminating the number of problems “cover pillar loop scratch” from 60 pcs in March 2020 to 0 in July 2020.